Involving stakeholders in the development of a dietary adoption concept: what can we learn from open innovation?. (24th April 2019) - Fink, Leonie; Ploeger, Angelika; Strassner, Carola
Part of the transformation to sustainable food systems is to increase the adoption rate of sustainable diets ideally by choice. At the same time evidence in the field of behavioural science shows that people have trouble translating their intentions into actual behaviour. This phenomenon, known as the intention-behaviour gap, is based on a number of barriers that influence actual behaviour. In search of an appropriate methodology to develop a dietary adoption concept supporting people's diet adoption processes, we examined the concept and especially the methods of open innovation, commonly applied in modern product and service development. This paper is about what we can learn or even transfer from open innovation to develop a dietary adoption concept. We reveal how the methods of open innovation can be usefully applied, such as integrating lead-users in the development process to let them find solutions to bridge the intention-behaviour gap.